Prevalence of malaria-helminth co-infections among children living in a setting of high coverage of standard interventions for malaria and helminths: Two population-based studies in Senegal - Muhammed O. Afolabi; Doudou Sow; Ibrahima Mbaye; Marie Pierre Diouf; Mor Absa Loum; Elhadji Babacar Fall; Amadou Seck; Isaac A. Manga; Cheikh Cissé; Baba Camara; Awa Diouf; Ndéye Aida Gaye; et al. (Frontiers Media S.A., 2023)
BackgroundConcurrent infections of Plasmodium falciparum with Soil Transmitted Helminths (STH) and Schistosoma spp are still a major public health problem among children living in Sub-Saharan Africa. We conducted two prospective studies among children living in urban and rural settings of Senegal, where control programmes for malaria, STH and schistosomiasis have been sustained, to determine the prevalence of malaria-helminth co-infection.MethodsWe enrolled 910 children aged 1-14 years from Saraya and Diourbel districts of Senegal in June and November 2021, respectively. We collected finger-prick blood samples from the children for malaria parasite detection using microscopy and PCR methods. Stool samples were also collected and Kato-Katz and PCR methods were used to detect STH and S. mansoni; and Merthiolate-iodine-formalin (MIF) test for other intestinal protozoans. Urine samples were analyzed using a filtration test, Point of Care Circulating Cathodic Antigens (POC-CCA) and PCR methods for detection of S. haematobium. Statistical analyses were performed to compare the continuous and categorical variables across the two study sites and age groups, as well as using the adjusted Odds ratios (aOR) to explore risk factors for malaria-helminth co-infections.ResultsThe overall prevalence of polyparasitism with P. falciparum, STH, S. haematobium and S. mansoni among children in the two study sites was 2.2% (20/910) while prevalence of P. falciparum-S. haematobium co-infection was 1.1% (10/910); P. falciparum-S. mansoni 0.7% (6/910) and P. falciparum with any intestinal protozoan 2.4% (22/910). Co-infection was slightly higher among 5-14 year old children (17/629, 2.7%; 95% CI: 1.43-3.97) than 1-4 years (3/281, 1.1%; 95% CI: −0.12-2.32) and, in boys (13/567, 2.3%; 95% CI: 1.27-3.96) than girls (7/343, 2.1%; 95% CI: 0.52-3.48). Children aged 5-14 years (aOR = 3.37; 95% CI: 0.82-13.77, p = 0.09), who were boys (aOR = 1.44; 95% CI: 0.48-4.36, p = 0.51) and lived in Saraya (aOR = 1.27; 95% CI: 0.24-6.69, p = 0.77) had a higher risk of malaria-helminth co-infection than other age group, in girls and those who lived in Diourbel. Living in houses with spaces between the walls and roofs as well as frequent contacts with water during swimming were statistically significant risk factors for malaria-helminth co-infection.ConclusionsThe prevalence of malaria-helminth co-infection is low in two districts in Senegal, possibly due to sustained implementation of effective control measures for malaria and NTDs. These findings could help to develop and implement strategies that would lead to elimination of malaria and helminths in the study areas.